Primary hypothyroidism and the low T3 syndrome in thalassaemia major. Issue 2 (February 1983) - Sabato, A R; De Sanctis, V; Atti, G; Capra, L; Bagni, B; Vullo, C
Abstract : Basal thyroid function was assessed from the serum thyroxine, triiodothyronine, and thyroid-stimulating hormone concentrations in 114 patients (mean age 13·6 years), designated group 1, with thalassaemia major. Forty of these patients were further evaluated (group 2) for serum-free thyroxine, and free and reverse triiodothyronine concentrations. The response of thyroid-stimulating hormone to thyrotrophin-releasing hormone was measured in 25 patients from this subgroup. Results were compared with those from 53 control subjects. Primary hypothyroidism, defined by a raised thyroid-stimulating hormone level above the upper range limit of 6·5 μIU/ml of the controls, was present in 17·5% of the 114 patients. In group 2 patients, a spectrum of thyroid disease spanning uncompensated and compensated primary hypothyroidism and decreased thyroid reserve was evident. The presence of primary hypothyroidism (uncompensated and compensated) was associated with an age of at least 10 years, an increased incidence of iron toxicity-related systemic complications, and an increased transfusion iron load, but not with an increased serum ferritin level. In the total 114 patients there were 9 who had the low triiodothyronine (sick euthyroid) syndrome. Primary hypothyroidism occurs in a significant proportion of thalassaemia major patients in the absence of obvious clinical signs of hypothyroidism; the low triiodothyronine syndrome associated with non-thyroidal disease is not uncommon.